El indigenismo de la Unidad Popular (Chile 1970-1973). Estado y Nación entre reformismo y realidad - Francisco Albizú Labbé (Les Cahiers ALHIM)
This brief statement has two objectives: a) we propose some topics for reflection on the relations between the Latin American left and the so-called "indigenous question", b) we present some aspects of the indigenous experience of the Popular Unity government after win Salvador Allende, between the years 1970-1973. We indicate the special importance it acquired this historic moment in the indigenous world. We conclude emphasizing the dramatic contemporary situation of indigenous societies in Chile.